7
$\begingroup$

There seem to be a lot of posts on the subject of heat equations with weird boundary conditions, but after a brief perusal of these I couldn't find quite what I'm looking for. The following 1D problem has arisen in my research, and I'm not sure how best to solve it:

$$\frac{\partial u}{\partial t} = \frac{\partial^2 u}{\partial x^2}; \\u(0,t) = f(t); \\ \frac{\partial u}{\partial x}(0,t) = g(t)$$

on the interval $(x,t)\in[0,\infty)\times (-\infty,\infty)$, where $f$ and $g$ are some specified smooth functions.

First of all: is this problem even well-posed? I don't know much existence/uniqueness theory for PDEs so I'm not sure.

Secondly, how can I go about solving this equation analytically? The unusual, nonhomogeneous B.C.'s are really tripping me up.


EDIT: Here's what I've tried. Letting $\tilde{u}(x,\omega)=\int dt \, e^{-i\omega t} u(x,t),$ we can transform the original equation into a 2nd order ODE in $x$ with Cauchy boundary conditions and solution

$$\tilde{u}(x,\omega) = \tilde{f}(\omega) \cosh\left((1-i)\sqrt{\frac{\omega}{2}}x\right)+\frac{1+i}{\sqrt{2\omega}}\tilde{g}(\omega) \sinh\left((1-i)\sqrt{\frac{\omega}{2}}x\right),$$

where $\tilde{f}$ and $\tilde{g}$ are of course the Fourier transforms of $f$ and $g$ respectively.

Formally, then, \begin{align}u(x,t) &= \int \frac{d\omega}{2\pi} \, e^{i \omega t} \left[ \tilde{f}(\omega) \cosh\left((1-i)\sqrt{\frac{\omega}{2}}x\right)+\frac{1+i}{\sqrt{2\omega}}\tilde{g}(\omega) \sinh\left((1-i)\sqrt{\frac{\omega}{2}}x\right) \right] \\ &=\int \frac{d \omega}{2 \pi} \int d\tau \, e^{i\omega(t-\tau)}\left[f(\tau) \cosh\left((1-i)\sqrt{\frac{\omega}{2}}x\right)+\frac{1+i}{\sqrt{2\omega}}g(\tau) \sinh\left((1-i)\sqrt{\frac{\omega}{2}}x\right)\right] \\ &= \int_{-\infty}^\infty d\tau \, \left(F(x,t-\tau)f(\tau)+G(x,t-\tau)g(\tau)\right), \end{align} where $$F(x,t):= \int_{-\infty}^{\infty} \frac{d\omega}{2\pi} \, e^{i \omega t} \cosh\left((1-i)\sqrt{\frac{\omega}{2}}x\right)$$

and

$$G(x,t):= \int_{-\infty}^{\infty} \frac{d\omega}{2\pi} \, e^{i \omega t} \frac{1+i}{\sqrt{2\omega}} \sinh\left((1-i)\sqrt{\frac{\omega} {2}}x\right). $$

I am getting discouraged, however, attempting to evaluate the kernels $F$ and $G$, which besides simply being challenging (for me anyway) to work with, appear to suffer from divergences.

Have I done something wrong? Are there closed-form, or at least nicer, expressions for $F$ and $G$? Does this approach even work?

$\endgroup$
  • 1
    $\begingroup$ Regarding existence: if we look at it from a numerical point of view with $C = \frac{\Delta t}{\Delta x^2}$ and $u_{i,j} = u(i\Delta x, j\Delta t)$ then discretizing $u_t = u_{xx}$ to second order leads to the recursion $$u_{i+1,j} = \frac{u_{i,j+1} - u_{i,j} + C[2u_{i,j} - u_{i-1,j}]}{C}$$ which can in principle be propagated to give us $u_{i,j}$ for all $i,j$ as the BC gives us $u_{0,j}$ and $u_{1,j}$. This is by far no proof of existence, but it suggest there might be just enough information in the BC to allow us to compute a solution at least locally around $x=0$ for all $t$. $\endgroup$ – Winther Jan 24 '17 at 0:11
  • $\begingroup$ I think this problem is ill poised. There can not be simultaneously 2 different boundary conditions for heat equation at $x=0$. The origin of the problem might be in some incorrect physical assumptions in the model. $\endgroup$ – Nemo Jan 25 '17 at 13:14
  • $\begingroup$ @Nemo "There can not be simultaneously 2 different boundary conditions for heat equation at $x=0$." care to explain why not or share a reference? $\endgroup$ – mikefallopian Jan 25 '17 at 20:11
  • $\begingroup$ @mikefallopian is anything wrong with my answer? Are there any countering objections? $\endgroup$ – Nemo Jan 26 '17 at 11:53
  • $\begingroup$ @Nemo That might be, however I’m afraid the proof below is not a valid one. Note that a system can seem to be overdetermined and still have a solution. To show that it’s ill defined in your approach you have to show that no matter what initial condition $v_0(x)$ you choose then you cannot satisfy the second boundary condition and I don't see that. $\endgroup$ – Winther Jan 26 '17 at 13:47
0
$\begingroup$

Approach $1$: separation of variables

Case $1$: $\text{Re}(t)\geq0$

Let $u(x,t)=X(x)T(t)$ ,

Then $X(x)T'(t)=X''(x)T(t)$

$\dfrac{T'(t)}{T(t)}=\dfrac{X''(x)}{X(x)}=-s^2$

$\begin{cases}\dfrac{T'(t)}{T(t)}=-s^2\\X''(x)+s^2X(x)=0\end{cases}$

$\begin{cases}T(t)=c_3(s^2)e^{-ts^2}\\X(x)=\begin{cases}c_1(s^2)\sin xs+c_2(s^2)\cos xs&\text{when}~s\neq0\\c_1x+c_2&\text{when}~s=0\end{cases}\end{cases}$

$\therefore u(x,t)=C_1x+C_2+\int_0^\infty C_3(s^2)e^{-ts^2}\sin xs~ds+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds$

$\dfrac{\partial u(x,t)}{\partial x}=C_1+\int_0^\infty sC_3(s^2)e^{-ts^2}\cos xs~ds-\int_0^\infty sC_4(s^2)e^{-ts^2}\sin xs~ds$

$\dfrac{\partial u(x,t)}{\partial x}(x=0)=g(t)$ :

$C_1+\int_0^\infty sC_3(s^2)e^{-ts^2}~ds=g(t)$

$\int_0^\infty\dfrac{C_3(s^2)e^{-ts^2}}{2}d(s^2)=g(t)-C_1$

$\int_0^\infty\dfrac{C_3(s)e^{-ts}}{2}ds=g(t)-C_1$

$\mathcal{L}_{s\to t}\biggl\{\dfrac{C_3(s)}{2}\biggr\}=g(t)-C_1$

$C_3(s)=2\mathcal{L}^{-1}_{t\to s}\{g(t)\}-2C_1\delta(s)$

$\therefore u(x,t)=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-2C_1\int_0^\infty\delta(s^2)e^{-ts^2}\sin xs~ds+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-C_1\int_0^\infty\dfrac{\delta(s^2)e^{-ts^2}\sin xs}{s}d(s^2)+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-C_1\int_0^\infty\dfrac{\delta(s)e^{-ts}\sin x\sqrt{s}}{\sqrt{s}}ds+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-C_1\lim\limits_{s\to 0}\dfrac{e^{-ts}\sin x\sqrt{s}}{\sqrt{s}}+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-C_1\lim\limits_{s\to 0}\dfrac{\dfrac{xe^{-ts}\cos x\sqrt{s}}{2\sqrt{s}}-te^{-ts}\sin x\sqrt{s}}{\dfrac{1}{2\sqrt{s}}}+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-C_1\lim\limits_{s\to 0}(xe^{-ts}\cos x\sqrt{s}-2t\sqrt{s}e^{-ts}\sin x\sqrt{s})+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds-C_1x+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds=C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds+\int_0^\infty C_4(s^2)e^{-ts^2}\cos xs~ds$

$u(0,t)=f(t)$ :

$C_2+\int_0^\infty C_4(s^2)e^{-ts^2}~ds=f(t)$

$\int_0^\infty\dfrac{C_4(s^2)e^{-ts^2}}{2s}d(s^2)=f(t)-C_2$

$\int_0^\infty\dfrac{C_4(s)e^{-ts}}{2\sqrt{s}}ds=f(t)-C_2$

$\mathcal{L}_{s\to t}\biggl\{\dfrac{C_4(s)}{2\sqrt{s}}\biggr\}=f(t)-C_2$

$C_4(s)=2\sqrt{s}\mathcal{L}^{-1}_{t\to s}\{f(t)\}-C_2\delta(\sqrt{s})$

$\therefore u(x,t)=C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(t)\}e^{-ts^2}\cos xs~ds-C_2\int_0^\infty\delta(s)e^{-ts^2}\cos xs~ds=C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(t)\}e^{-ts^2}\cos xs~ds-C_2=2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(t)\}e^{-ts^2}\cos xs~ds$

Case $2$: $\text{Re}(t)\leq0$

Let $u(x,t)=X(x)T(t)$ ,

Then $X(x)T'(t)=X''(x)T(t)$

$\dfrac{T'(t)}{T(t)}=\dfrac{X''(x)}{X(x)}=s^2$

$\begin{cases}\dfrac{T'(t)}{T(t)}=s^2\\X''(x)-s^2X(x)=0\end{cases}$

$\begin{cases}T(t)=c_3(s^2)e^{ts^2}\\X(x)=\begin{cases}c_1(s^2)\sinh xs+c_2(s^2)\cosh xs&\text{when}~s\neq0\\c_1x+c_2&\text{when}~s=0\end{cases}\end{cases}$

$\therefore u(x,t)=C_1x+C_2+\int_0^\infty C_3(s^2)e^{ts^2}\sinh xs~ds+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds$

$\dfrac{\partial u(x,t)}{\partial x}=C_1+\int_0^\infty sC_3(s^2)e^{ts^2}\cosh xs~ds+\int_0^\infty sC_4(s^2)e^{ts^2}\sinh xs~ds$

$\dfrac{\partial u(x,t)}{\partial x}(x=0)=g(t)$ :

$C_1+\int_0^\infty sC_3(s^2)e^{ts^2}~ds=g(t)$

$\int_0^\infty\dfrac{C_3(s^2)e^{ts^2}}{2}d(s^2)=g(t)-C_1$

$\int_0^\infty\dfrac{C_3(s)e^{ts}}{2}ds=g(t)-C_1$

$\int_0^\infty\dfrac{C_3(s)e^{-ts}}{2}ds=g(-t)-C_1$

$\mathcal{L}_{s\to t}\biggl\{\dfrac{C_3(s)}{2}\biggr\}=g(-t)-C_1$

$C_3(s)=2\mathcal{L}^{-1}_{t\to s}\{g(-t)\}-2C_1\delta(s)$

$\therefore u(x,t)=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-2C_1\int_0^\infty\delta(s^2)e^{ts^2}\sinh xs~ds+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-C_1\int_0^\infty\dfrac{\delta(s^2)e^{ts^2}\sinh xs}{s}d(s^2)+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-C_1\int_0^\infty\dfrac{\delta(s)e^{ts}\sinh x\sqrt{s}}{\sqrt{s}}ds+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-C_1\lim\limits_{s\to 0}\dfrac{e^{ts}\sinh x\sqrt{s}}{\sqrt{s}}+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-C_1\lim\limits_{s\to 0}\dfrac{\dfrac{xe^{ts}\cosh x\sqrt{s}}{2\sqrt{s}}+te^{ts}\sinh x\sqrt{s}}{\dfrac{1}{2\sqrt{s}}}+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-C_1\lim\limits_{s\to 0}(xe^{ts}\cosh x\sqrt{s}+2t\sqrt{s}e^{ts}\sinh x\sqrt{s})+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_1x+C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds-C_1x+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds=C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds+\int_0^\infty C_4(s^2)e^{ts^2}\cosh xs~ds$

$u(0,t)=f(t)$ :

$C_2+\int_0^\infty C_4(s^2)e^{ts^2}~ds=f(t)$

$\int_0^\infty\dfrac{C_4(s^2)e^{ts^2}}{2s}d(s^2)=f(t)-C_2$

$\int_0^\infty\dfrac{C_4(s)e^{ts}}{2\sqrt{s}}ds=f(t)-C_2$

$\int_0^\infty\dfrac{C_4(s)e^{-ts}}{2\sqrt{s}}ds=f(-t)-C_2$

$\mathcal{L}_{s\to t}\biggl\{\dfrac{C_4(s)}{2\sqrt{s}}\biggr\}=f(-t)-C_2$

$C_4(s)=2\sqrt{s}\mathcal{L}^{-1}_{t\to s}\{f(-t)\}-C_2\delta(\sqrt{s})$

$\therefore u(x,t)=C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(-t)\}e^{ts^2}\cosh xs~ds-C_2\int_0^\infty\delta(s)e^{ts^2}\cosh xs~ds=C_2+2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(-t)\}e^{ts^2}\cosh xs~ds-C_2=2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(-t)\}e^{ts^2}\cosh xs~ds$

Hence $u(x,t)=\begin{cases}2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(t)\}e^{-ts^2}\sin xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(t)\}e^{-ts^2}\cos xs~ds&\text{when Re}(t)\geq0\\2\int_0^\infty\mathcal{L}^{-1}_{t\to s^2}\{g(-t)\}e^{ts^2}\sinh xs~ds+2\int_0^\infty s\mathcal{L}^{-1}_{t\to s^2}\{f(-t)\}e^{ts^2}\cosh xs~ds&\text{when Re}(t)\leq0\end{cases}$

Approach $2$: power series method

Similar to diffusion equation, inhomogenous boundary conditions (the subtraction method):

Let $u(x,t)=\sum\limits_{n=0}^\infty\dfrac{x^n}{n!}\dfrac{\partial^nu(0,t)}{\partial x^n}$ ,

Then $u(x,t)=\sum\limits_{n=0}^\infty\dfrac{x^{2n}}{(2n)!}\dfrac{\partial^{2n}u(0,t)}{\partial x^{2n}}+\sum\limits_{n=0}^\infty\dfrac{x^{2n+1}}{(2n+1)!}\dfrac{\partial^{2n+1}u(0,t)}{\partial x^{2n+1}}=\sum\limits_{n=0}^\infty\dfrac{x^{2n}}{(2n)!}\dfrac{\partial^nu(0,t)}{\partial t^n}+\sum\limits_{n=0}^\infty\dfrac{x^{2n+1}}{(2n+1)!}\dfrac{\partial^nu_x(0,t)}{\partial t^n}=\sum\limits_{n=0}^\infty\dfrac{x^{2n}}{(2n)!}\dfrac{\partial^nf(t)}{\partial t^n}+\sum\limits_{n=0}^\infty\dfrac{x^{2n+1}}{(2n+1)!}\dfrac{\partial^ng(t)}{\partial t^n}$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.